(untitled) - Adam, Everett E. (Englewood Cliffs, NJ, 1992)
In this new text, the author blends accessible coverage of quantitative methods with engaging qualitative topics. Meaningful examples clearly illustrate the logic and analytical thought process of modeling, and behavioral analysis is included in the use and implementation of analytical models. With a unique chapter of plant tours early in the book, students get a real-world, practical orientation throughout the text. On the Job" boxes- profiles of people in professions outside of operations who use operations management concepts daily- demonstrate the importance of Operations management to non-majors. Quantitative and qualitative issues are fully integrated. Extended examples and real-world cases show students the range of analysis needed to manage, and how these tools are complementary rather than mutually exclusive.
Keywords: Production management